1999
DOI: 10.1046/j.1365-2915.1999.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual responses of Musca domestica to pheromone impregnated targets in poultry units

Abstract: Field trials investigating the effect of visual cues on catches of Musca domestica (Diptera: Muscidae) at toxic targets impregnated with the female sex pheromone (Z)-9-tricosene, were conducted in a caged-layer deep-pit poultry unit in southern England. Targets treated with azamethiphos and baited with 2.5 g of 40% (Z)-9-tricosene impregnated beads caught significantly greater numbers of M. domestica than control targets. The greater attractiveness of the pheromone impregnated targets persisted for at least 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…The response of newly emerged flies to ( Z )‐9‐tricosene is not a strong as that shown by older individuals ( Silhacek et al., 1972). Finally, the more rapid decline in efficacy that we observed compared to Chapman et al. (1998a,b, 1999) may simply be because of exposure to the elements removing the active ingredients from the targets in outdoor situations.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The response of newly emerged flies to ( Z )‐9‐tricosene is not a strong as that shown by older individuals ( Silhacek et al., 1972). Finally, the more rapid decline in efficacy that we observed compared to Chapman et al. (1998a,b, 1999) may simply be because of exposure to the elements removing the active ingredients from the targets in outdoor situations.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, mobile houseflies are more highly concentrated in and around animal rearing units than they are on landfill, and it is not surprising that in these situations tricosene‐impregnated traps are effective at attracting large numbers of flies. More recently a series of field trials in closed poultry units reported variable catches of 70–200 houseflies per day ( Chapman et al., 1998a,b, 1999), underscoring the high density of fly populations in animal units and the efficiency of lure‐and‐kill traps in enclosed conditions. Chapman et al's targets also continued to attract flies for up to 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This predisposition of house flies to seek sugar sources for their survival presents an opportunity to use sugar in toxic baits. For this reason, sugar along with toxicant, water and/or other attractant, in many other studies, has been an essential component in making toxic baits successful [6,10-13]. …”
Section: Introductionmentioning
confidence: 99%
“…Yellow, for example, was found to be most attractive to house flies when used in jug traps [18]. In another study, black was found to be the most attractive to house flies [13], however, Geden [14] reported that blue fabric targets were more attractive to house flies than black targets. Although colors have been used in making traps attractive, studies on the use of colors, to the best of the authors’ knowledge, are rare in making toxic baits attractive to house flies particularly in Pakistan.…”
Section: Introductionmentioning
confidence: 99%